2020
DOI: 10.1097/jcn.0000000000000722
|View full text |Cite
|
Sign up to set email alerts
|

The 10-Year Prognosis and Prevalence of Brugada-Type Electrocardiograms in Elderly Women

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Furthermore, women diagnosed with BrS are less likely to experience arrhythmic events (syncope, aborted cardiac arrest, and documented ventricular fibrillation) ( 18 , 19 ). Following similar data, BrS ECG patterns are not uncommon in elderly women, but are not associated with an increased risk of mortality ( 21 , 22 ). Recently, a new study demonstrated that women with BrS less frequently presented with a type 1 ECG pattern, had a higher rate of family history of SCD, and had less sustained ventricular arrhythmias on electrophysiological study, despite not constituting a risk-free group.…”
Section: Clinical Findingsmentioning
confidence: 52%
See 1 more Smart Citation
“…Furthermore, women diagnosed with BrS are less likely to experience arrhythmic events (syncope, aborted cardiac arrest, and documented ventricular fibrillation) ( 18 , 19 ). Following similar data, BrS ECG patterns are not uncommon in elderly women, but are not associated with an increased risk of mortality ( 21 , 22 ). Recently, a new study demonstrated that women with BrS less frequently presented with a type 1 ECG pattern, had a higher rate of family history of SCD, and had less sustained ventricular arrhythmias on electrophysiological study, despite not constituting a risk-free group.…”
Section: Clinical Findingsmentioning
confidence: 52%
“…A personalized approach should be done before ICD implantation. At our acknowledgement, the first and only study focused on elderly BrS women was published in 2020, showing a not infrequent BrS pattern in the ECG but associated with a lower risk of malignant arrhythmias and SCD ( 21 ).…”
Section: Age Differences In Womenmentioning
confidence: 99%